Demethylzeylasteral reduces the level of proteinuria in diabetic nephropathy: Screening of network pharmacology and verification by animal experiment - Lengnan Xu; Ban Zhao; Liping Yang; Xinyi Dong; Xue Yang; Yonghui Mao (Wiley, 2022)
Abstract This study aimed to use network pharmacology to detail the natural components isolated from Triptergium wilfordii Hook F (TwHF) and examine the effect of the main component (demethylzeylasteral, DEM) on rat models of diabetic nephropathy (DN). In this study, we used network pharmacology to detail the natural components isolated from TwHF, referenced a gene library when screening for components effective in the management of DN, and DEM was confirmed in DN rats. All data were analyzed using the Discovery Studio 4.5 System and the systems Dock online docking method platform. All 24 rats were divided into 4 groups: control, DN, TwHF, and DEM. Blood and urine samples were tested at 0, 8, and 12 weeks. Renal histopathological changes were scored. Network pharmacology indicated that 370 compounds and 46 small molecules (including DEM) were biologically active constituents of TwHF, mainly affecting the inflammatory response through PI3K‐Akt and Jak-STAT pathways. Proteinuria in the TwHF and DEM groups was significantly lower than in the DN group (p ≤ .001), and the decrease in proteinuria in the DEM group was more obvious than in the TwHF group (p = .004). The tubular interstitial scores were better in the DEM group than in the TwHF and DN groups. These results indicate that DEM effectively reduced proteinuria and alleviated the tubular interstitial changes in rat models of DN, which may be provide a scientific foundation for the development of novel drugs for treatment of DN.